Advances in Biotechnological Strategies for Sustainable Production of Non-Animal Proteins: Challenges, Innovations, and Applications - Emanuel do Nascimento Muniz; Rebeca Teixeira de Queiroz Montenegro; Daniel Nascimento da Silva; Alan Portal D’Almeida; Luciana Rocha Barros Gonçalves; Tiago Lima de Albuquerque (Fermentation, 2024)
This review explores recent advances in the design of fermentation processes for producing alternative proteins, focusing on utilizing agro-industrial waste and renewable substrates. New bioprocess strategies, such as experimental designs, optimizing bioreactors, bioprocesses, and applying precision fermentation can improve the protein yields and nutritional value. Also, unconventional substrates, such as hydrolysates derived from agro-industrial residues conversion may result in cost reduction and enhanced feasibility. The application of enzymes to produce protein-rich foods with high bioaccessibility that improve digestibility and nutritional value are also highlighted. This article addresses the importance of developing cost-effective fermentation solutions that minimize the environmental impact while addressing technical challenges such as scalability and contamination control. Furthermore, it emphasizes the growing need for innovations in fermentation process design to ensure the sustainability of industrial protein production. The review concludes that improvements in process design are fundamental in overcoming technological and regulatory barriers, particularly in increasing the efficiency and competitiveness of non-meat proteins in the global market.